Pemikiran Pendidikan Karakter Al-Ghazali dan Thomas Lichona - Zaimuddin (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
This paper aims to find out how the reconstruction of al-Ghazali's educational thinking in contemporary Islamic education. The benefit is that the government and educators can use al-Ghazali's educational thinking as an inspiration in upholding quality Indonesian education. The result of this paper is that the building of al-Ghazali's educational thought is religious-ethical. Al-Ghazali's educational goals cover three aspects, namely cognitive aspects, affective aspects, and psychomotor aspects. In addition, it places two important things as educational orientations, namely achieving human perfection to qualitatively draw closer to Allah SWT; and achieve human perfection to achieve happiness in this world and the hereafter. An educator is a person who masters a discipline and is able to practice it as well as a human figure who totally concentrates on the field of education. Students are placed as objects as well as subjects and set ten ideal criteria that must be pursued by students in order to succeed in education. Al-Ghazali mentions four categories of classification of science, namely; classification of syar'iyah science (religion) and 'aqliyah (reason); theoretical and practical science; knowledge presented (hudhûri) and acquired (hushli); Science fardhu 'ain and fard kifâyah. Al-Ghazali's teaching method emphasizes that teachers who provide knowledge are required to use exemplary methods and dialogue in the learning process. Thomas Lickona states that the notion of character education is a deliberate effort to help a person so that he can understand, pay attention to, and practice core ethical values. And more broadly he said that character education is a deliberate (conscious) effort to realize virtue, namely objectively good human qualities, not only good for individuals, but also good for society as a whole.79 Thomas Lickona also defines character education as an effort deliberately from all dimensions of social life to help shape character optimally.